'Not Music but Sonic Porn': Identity Politics, Social Reform, and the Negative Reception of Jazz. Issue 1 (April 2021) - Rastrick, Ólafur
Abstract : The 1920s fascination with jazz music and dance provoked deep concern and anxiety about the future direction of society in different corners of the world. Jazz was readily associated with various social evils that were considered a threat to the cultural and moral wellbeing of nations as well as the mental and physical health of both individuals and society in general. Negative reception of jazz was not limited to the United States but seems to have expanded around the globe just as rapidly as the appeal of the music and movements loosely identified at the time as jazz. The article identifies defining elements of this negative discourse to explore their mechanism and bearings in particular localized settings, namely, in Australia and Iceland. The focus is on how the perceptions of jazz as a social evil contributed to conceptualizing ideas of social reform and how the demonization of jazz played a role in defining national character and culture. Australia and Iceland serve as examples for understanding the way in which the negative discourse gained a foothold in society by relating to pre-existing social anxieties, political objectives and historical context.